Epidemiology of Bacterial Meningitis in the Nine Years Since Meningococcal Serogroup A Conjugate Vaccine Introduction, Niger, 2010–2018. (31st October 2019) - Sidikou, Fati; Potts, Caelin C; Zaneidou, Maman; Mbaeyi, Sarah; Kadadé, Goumbi; Paye, Marietou F; Ousmane, Sani; Issaka, Bassira; Chen, Alexander; Chang, How-Yi; Issifou, Djibo; Lingani, Clement; et al.
Abstract: Background: In 2010, Niger and other meningitis belt countries introduced a meningococcal serogroup A conjugate vaccine (MACV). We describe the epidemiology of bacterial meningitis in Niger from 2010 to 2018. Methods: Suspected and confirmed meningitis cases from January 1, 2010 to July 15, 2018 were obtained from national aggregate and laboratory surveillance. Cerebrospinal fluid specimens were analyzed by culture and/or polymerase chain reaction. Annual incidence was calculated as cases per 100 000 population. Selected isolates obtained during 2016–2017 were characterized by whole-genome sequencing. Results: Of the 21 142 suspected cases of meningitis, 5590 were confirmed: Neisseria meningitidis ([Nm] 85%), Streptococcus pneumoniae ([Sp] 13%), and Haemophilus influenzae ([Hi] 2%). No NmA cases occurred after 2011. Annual incidence per 100 000 population was more dynamic for Nm (0.06–7.71) than for Sp (0.18–0.70) and Hi (0.01–0.23). The predominant Nm serogroups varied over time (NmW in 2010–2011, NmC in 2015–2018, and both NmC and NmX in 2017–2018). Meningococcal meningitis incidence was highest in the regions of Niamey, Tillabery, Dosso, Tahoua, and Maradi. The NmW isolates were clonal complex (CC)11, NmX were CC181, and NmC were CC10217. Conclusions: After MACV introduction, we observed an absence of NmA, the emergence and continuing burden of NmC, and an increase in NmX. Niger's dynamic Nm serogroup distribution highlights the need for strong surveillance programs to inform vaccine policy.